Effect of ski-boot design on flexural and rebound performances - Colonna, M.; Nicotra, M.; Moncalero, M.; Fiorini, M. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The aim of this work is to analyze how design and materials affect the performances (flex and rebound) of ski-boots, highlighting the possibility to select the proper ski-boot design on the basis of skiing discipline and type of skiing.